Pengembangan Media Pembelajaran Interaktif Berbasis Contextual Teaching and Learning terhadap Motivasi Belajar Siswa SMA pada Pembelajaran Kimia Materi Sistem Periodik - Astri Wahyuni; Haryanto Haryanto; Firdiawan Ekaputra; Zurweni Zurweni; Afrida Afrida (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2026)
This study was motivated by the low level of students’ learning motivation in the topic of the Periodic System of Elements, which is caused by the abstract and complex nature of the material as well as the limited use of engaging and contextual learning media. This research aimed to develop an interactive learning media integrated with the Contextual Teaching and Learning (CTL) approach and to determine its feasibility, students’ responses, and its effectiveness in improving learning motivation. The research employed a Research and Development (R&D) method using the Lee and Owens model, which consists of analysis, design, development, implementation, and evaluation stages. The developed product was an interactive learning media based on Genially, incorporating text, images, videos, animations, quizzes, and the seven components of CTL. The trial subjects were Grade X students, conducted through one-to-one and small group evaluations. The research instruments included validation questionnaires, student response questionnaires, and learning motivation questionnaires. The results indicated that the developed media was highly feasible, with student responses reaching 86.6% in the one-to-one test and 87.6% in the small group test, both categorized as very good. Furthermore, students’ learning motivation increased significantly from 50.7% to 79%, categorized as high. These findings imply that the integration of interactive media with the CTL approach can effectively enhance students’ learning motivation by providing meaningful, contextual, and engaging learning experiences. Therefore, this media can be used as an alternative instructional tool to support chemistry learning, particularly in improving students’ motivation in understanding abstract concepts such as the Periodic System of Elements.